Sintesis Bioetanol Dari Jerami Padi (Oryza sativa L) Melalui Fermentasi - Said, Muhammad; Diah, Anang Wahid M.; Sabang, Sri Mulyani (Universitas Tadulako, 2014)
Rice straw is an agricultural waste into organic waste further. Rice straw can be utilized as an alternative energy that is bioethanol. The objective of this research was to determine the optimal concentration of ethanol by the duration of fermentation. This research applied fermentation to rice straw using yeast bread in various times of 7, 10, 13, 16, 19, and 22 days. The steps of this research were sample preparation, delignification, hydrolysis, and fermentation. Bioethanol from fermented rice straw was analysed using alcoholmeter. The products of fermented ethanol increased and reached the optimum at day 13, which was 4.83+0.05%, then decrease the ethanol content at day 16, 19, and 22.